Hexose transporter CsSWEET7a in cucumber mediates phloem unloading in companion cells for fruit development. Issue 1 (5th February 2021) - Li, Yaxin; Liu, Huan; Yao, Xuehui; Wang, Jiang; Feng, Sheng; Sun, Lulu; Ma, Si; Xu, Kang; Chen, Li-Qing; Sui, Xiaolei
Abstract: In the fleshy fruit of cucumbers ( Cucumis sativus L.), the phloem flow is unloaded via an apoplasmic pathway, which requires protein carriers to export sugars derived from stachyose and raffinose into the apoplasm. However, transporter(s) involved in this process remain unidentified. Here, we report that a hexose transporter, CsSWEET7a (Sugar Will Eventually be Exported Transporter 7a), was highly expressed in cucumber sink tissues and localized to the plasma membrane in companion cells of the phloem. Its expression level increased gradually during fruit development. Down-regulation of CsSWEET7a by RNA interference (RNAi) resulted in smaller fruit size along with reduced soluble sugar levels and reduced allocation of 14 C-labelled carbon to sink tissues. CsSWEET7a overexpression lines showed an opposite phenotype. Interestingly, genes encoding alkaline α-galactosidase (AGA) and sucrose synthase (SUS) were also differentially regulated in CsSWEET7a transgenic lines. Immunohistochemical analysis demonstrated that CsAGA2 co-localized with CsSWEET7a in companion cells, indicating cooperation between AGA and CsSWEET7a in fruit phloem unloading. Our findings indicated that CsSWEET7a is involved in sugar phloem unloading in cucumber fruit by removing hexoses from companion cells to the apoplasmic space to stimulate the raffinose family of oligosaccharides (RFOs) metabolism so that additional sugars can be unloaded to promote fruit growth. This study also provides a possible avenue towards improving fruit production in cucumber. Abstract : Transporter CsSWEET7a removes hexose from companion cells to the apoplasmic space to stimulate fruit phloem unloading so that additional sugars can be unloaded to promote fruit growth.